DETEKSI CACAT PADA CARBON FIBER REINFORCED POLYMER BERDASARKAN KOEFISIEN KORELASI PEARSON DARI SINYAL ECHO ULTRASONIK - Yusuf Giri Wijaya; Suprijanto Suprijanto; Afid Nugroho; Rhakamerta Hijazi; Damar Rastri Adhika (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2024)
Carbon fiber reinforced polymer (CFRP) is a composite material widely used in the aerospace, automotive, and marine industries due to its high strength and low weight. However, the reliability of CFRP can be compromised by internal defects occurring during manufacturing or use. This study aims to detect defects in CFRP using the Pearson correlation coefficient from ultrasonic echo signals. This method utilizes ultrasonic waves to identify defects based on changes in signal patterns. The reference signal is obtained by averaging the signals from several defect-free locations. Variations in the measurement signals compared to the reference signal are quantified using the Pearson correlation coefficient to classify defect-free and defect-containing areas. The test samples consisted of thin CFRP plates with artificial defects created using Teflon material in the form of circles with a radius of 15 mm, placed at two different depths. The results indicate that the Pearson correlation coefficient effectively distinguishes between defect-free and defective areas. Defect-free areas showed correlation values in the range of 0.97 to 1, while defective areas showed low correlation values in the range of 0 to 0.36.